التحقيق العقاري الجماعي - رشيدة سلطاني, -فاطمة بني (Universté ELOUEd-جامعة الوادي, 2020)
أدى التأخر في التطهير الشامل للملكية العقارية الخاصة عبر كامل الت ا رب الوطني، وفشل نظام عقد 176 المؤرخ في 63 ماي 3871 إلى زيادة الن ا زعات القضائية / الشهرة المنصوص عليه في المرسوم 71 وتعطل المشاريع التنموية، بات على المشرع إيجاد آلية جديدة تواكب وتيرة الإصلاحات الاقتصادية، تدعى 76 المؤرخ في 60 فيفري 6770 المتضمن تأسيس إج ا رء / بالتحقيق العقاري وذلك بموجب القانون 70 معاينة حق الملكية ويتم بالموا ا زة مع عمليات إعداد المسح العام للأ ا رضي وبصفة مستقلة عنه. يمكن هذا الاج ا رء الدولة عن طريق هيئاتها الإقليمية من المبادرة بفتح تحقيق عقاري جماعي في إطار انجاز بناء أو تهيئة عقارية ريفية أو حضرية، م أجل تسليم سندات الملكية لشاغلي هذه المناطق وتفادي عرقلة إنجاز وتطهير الأوعية العقارية لتشجيع الإستثمار المرتبط بتفعيل القروض العقارية وخلق سوق عقاري حر ي ا رعي التحديد الدقيق والمعرفة المسبقة للعقا ا رت والحقوق العينية للمتعاملين الوطنيين والأجانب ويضمن مخاطر القروض.The delay in a massive cleansi of private real estate selte property accross the national terretory resulted , and the failure of the private goodwill contract system stipulated in Decree N 352/83 of 21st May 1983 resulted into an increase in legal disputes and the disruption of development projects. The project now has to find a new mechanism to keep pace with pace of economic reforms, called the real estate investigation, according to law 02/07 dated on 27th February 2007 , which includes the establishment of a property right inspection procedure that is carried ont in parallel with the processes of preparing the general survey of lands independently of it. This mesure enables the state, through its regional bodies, to initiate a collective investigation in the context of the completion of a rural or urban construction or preparation in order to hand over the title deeds to the occupants of these areas. and to avoid obstructing the bias and clearing of real estate Containers to encourage associated investment related to the activation of real estate loans and the Creation of a free real estate market that takes into account the precise definition and knowledge Advance real estate and in-Kind - rights for national and foreign dealers and guarantee arantee loan risk .
مذكرة ماستر
Keywords: إيجاد آلية جديدة تواكب وتيرة الإصلاحات الاقتصادية